(3GdaQGFV GdfUjQjIs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s ((3egOi Hf GdMSf Hf eMeO GdfjQei GdLQLGfi s)
(3ChdgG (B:s
(3gPg CUhd hLed ef Yde GdaQGFV heG jJYdb HgG JYdb GdYGQV s
(3BNQgG (B:s
(3hdYegG GKfGf hdYeJgG hGMOI hgPG gh GdLhGH YfgG s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3JHUQGJ GdCUd (B:s
(3GdfSNI ebQhAI ef YGde eYQha (B: (3eMeO Hf GdGUQ Hf MeRI GdYdhi GdMSjfi GdYQGbis
Keywords: (3Yde GdaQGFVs